A study on the issues and challenges in the appointment of female judges in Syariah courts in Malaysia: a case study of Kuala Lumpur and Putrajaya / Awie Ramane, Hanan Mohd Kamal and Rafinie Ramli - Ramane, Awie; Mohd Kamal, Hanan; Ramli, Rafinie (2012)
In 2006, the 73r Muzakarah (Conference) of the Fatwa Committee National Council of Islamic Religious Affairs Malaysia had laid out a fatwa allowing the appointment of woman as a Syariah judge. In the beginning, the contention given by public as to the released of the fatwa was strong. As a result, the appointment was only made in 2010, four years later after the released of the fatwa. By far, there are a small number of states in Malaysia that had effectively succeeded the appointment, namely the Federal Territories of Putrajaya and Kuala Lumpur, Malacca and Perlis. This research therefore, deems to search for the outmost issues from various perspectives. The research is conducted under a case study within the scope of Kuala Lumpur and Putrajaya. This research conduct will be looking into as to the extent the appointment had affected the structure of the Syariah court, as well as the administration purposes. Furthermore, it will also be looking at the appointment of the female judges in the Islamic Republic of Pakistan and the issues that had arisen. Extensive research was also done by carrying out interviews with our learned judges and experienced practising lawyer in identifying the real issues behind the appointment of woman in the Syariah judiciary in Malaysia.